2007
DOI: 10.1007/s11307-007-0085-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional Imaging of Cerebral Blood Flow and Glucose Metabolism in Parkinson’s Disease and Huntington’s Disease

Abstract: Brain imaging of cerebral blood flow and glucose metabolism has been playing key roles in describing pathophysiology of Parkinson's disease (PD) and Huntington's disease (HD), respectively. Many biomarkers have been developed in recent years to investigate the abnormality in molecular substrate, track the time course of disease progression, and evaluate the efficacy of novel experimental therapeutics. A growing body of literature has emerged on neurobiology of these two movement disorders in resting states and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 82 publications
4
42
0
Order By: Relevance
“…1,20,21 Human and animal studies indicate a strong linkage between CBF, glucose metabolic rate, neuronal firing rates, and related measures of oxidative metabolism. 22,23 Our sample of MCS patients had approximately a 50% reduction in global CBF compared with controls, with a decreased GM/WM ratio, which is much larger than previously reported coefficients of variation of 10%-15%. 6,8,9 Global depression of CBF in our patients could result from disproportionate loss of neurons in GM, such that metabolism in GM moves closer to that of WM (the latter consisting mostly of glial elements).…”
Section: Demographicsmentioning
confidence: 55%
“…1,20,21 Human and animal studies indicate a strong linkage between CBF, glucose metabolic rate, neuronal firing rates, and related measures of oxidative metabolism. 22,23 Our sample of MCS patients had approximately a 50% reduction in global CBF compared with controls, with a decreased GM/WM ratio, which is much larger than previously reported coefficients of variation of 10%-15%. 6,8,9 Global depression of CBF in our patients could result from disproportionate loss of neurons in GM, such that metabolism in GM moves closer to that of WM (the latter consisting mostly of glial elements).…”
Section: Demographicsmentioning
confidence: 55%
“…Indeed, the R6/2 mice were shown to develop glucose intolerance and glycosuria [12,13]. In HD patients, glucose metabolism was significantly decreased in striatum and temporal and frontal cortical lobes, in both preclinical and affected individuals, with marked striatal hypometabolism in later stages of the disease reflecting neuronal atrophy [4]. However, this relation was not found in another study, perhaps because the patients studied had different anthropometric features [11].…”
Section: Contextmentioning
confidence: 94%
“…This neurodegeneration leads to motor disturbance, most typically chorea, cognitive loss, and psychiatric manifestations [3]. Metabolic dysfunction is relatively common in this disease and may be caused by impaired glucose metabolism and changes in insulin sensitivity [4][5][6][7][8]. mHtt and its fragments can interfere with energy production, through interaction with a variety of key proteins involved in energy metabolism and some complexes of the mitochondrial respiratory chain, namely complex II/III [5,9].…”
Section: Contextmentioning
confidence: 99%
“…Briefly, the SSM is applied to multivoxel metabolic imaging data in a combined sample of scans from healthy subjects and patients. Once a pattern is identified that distinguishes one group from the other, its expression can be prospectively quantified on an individual basis [18,19], and the resulting subject scores can be correlated with clinical and physiological measures of interest. The SSM/PCA and related multivariate techniques are well suited to the study of circuit disorders, which are neurological diseases with stereotyped disturbances in brain network organization.…”
Section: Metabolic Network Mappingmentioning
confidence: 99%